Role of cytological examination in head neck masses - Munjal, Manish; Chopra, Ajay; Munjal, Shubham; Kalra, Shivam; Shukla, Khyati (International Journal Of Community Medicine And Public Health, 2020)
Background: Fine needle cytology can differentiate inflammatory and the neoplastic lesions. Moreover, the neoplastic lesions of the head and neck have a propensity to seed the subcutaneous tissues if overlying planes are widely violated, thereby fine needle cytology over an excision’s biopsy is the preferred choice. Methods: 106 patients with head and neck swelling were selected from the head-neck tumor clinic of the Oto-rhino-laryngology services, Dayanand medical college and hospital, Ludhiana, India. An analysis of the efficacy of fine needle aspiration cytology (FNAC) in the diagnosis of head and neck swellings was carried out. Results: Overall sensitivity of FNAC was 88.9% whereas overall specificity was 100%. Overall accuracy for salivary gland tumors was 100% for pleomorphic adenoma. FNAC from 50 subjects (56.2%) reported tubercular pathology. FNAC had to be repeated in 6.6% of the cases because of unsatisfactory smears. In 3 cases, false negative diagnosis was obtained and in 3 it was inconclusive. Conclusion: Properly executed FNAC is of the greater value in surgical practice with 88.9% sensitivity and 100% specificity.